Obsidian Hydration Dating of Proposed Paleoindian Artifacts from Tulare Lake, California. (2nd July 2020) - Rogers, Alexander K.; Yohe, Robert M.
ABSTRACT: In this article, we report an obsidian hydration dating (OHD) analysis of 32 obsidian artifacts from the Witt Archaeological Locality in Tulare County, California. The artifacts (Western stemmed points, concave base points, crescents) were recovered from agricultural contexts, where provenience is indeterminate. Effective hydration temperature (EHT) was computed from local meteorological records. Hydration rates were based on geochemical source and adjusted for EHT, and ages computed based on the square–root–of–time model. Of the mean OHD ages, 80% are in the 7, 000–9, 000 cal BP range. The probability that the actual ages could be Clovis or earlier (>∼13, 200 years) was computed based on the mean and standard deviation of the OHD ages.